Mobile student study planner - Chai, Jia Yuan (2020)
Students nowadays are of heavy workloads. Sometimes, they are not able to keep up with their studies due to time constraints or wide range of syllabuses coverage. Inefficient time management will cause them to have low productivity in studies. Therefore, this project entitled “Mobile Student Study Planner” is to implement a study planner as a mobile application with some added features as compared to the existing applications in the marketplace. One of the added features lacking in existing applications is to help students to arrange their tasks based on the priority order. In order to implement this feature, an scheduling algorithm is applied to calculate the priority value and an automatic time scheduler is implemented to schedule time to all the created tasks. Another added feature is sending a second notification. This added feature is proposed to minimise the possibility of inaccurate time allocation during the automated time scheduling. Hence, this project is aimed to implement these features into a study planner to make it more feature-rich. This project will be developed in Android platform.